Рак молочной железы и мелатонин - Сорочан, П.П.; Громакова, И.А; Прохач, Н.Э. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2007)
Рассматриваются экспериментальные данные относительно онкостатического действия мелатонина (М) в гормонозависимых опухолях молочной железы. Обсуждаются механизмы, обеспечивающие противоопухолевые эффекты М. Обосновывается целесообразность применения М в антиэстрогенной терапии при раке молочной железы. Ключевые слова: мелатонин, рак молочной железы, ароматаза, клеточный цикл, теломераза, инвазия. Experimental findings supporting an oncostatic role of melatonin in hormone-dependent mammary tumors are reviewed. The mechanisms of melatonin anti-tumor effect are discussed, including interaction with the tumor cell estrogen-dependent pathways, cell cycle length regulation, telomerase activity inhibition, modulation of fatty acid transport, and metabolism and anti-invasive characteristics of the hormone. Melatonin application is shown to be well-grounded in anti-estrogen therapy of breast cancer. Key Words: melatonin, breast cancer, melatonin receptors, aromatase, cell cycle, telomerase, invasion.